2016
DOI: 10.1039/c6ra20722g
|View full text |Cite
|
Sign up to set email alerts
|

Biologically synthesized crude calcium lactate as a substrate for propylene glycol production

Abstract: Lactic acid (LA) can be obtained easily through fermentation of saccharides, and is an extremely useful building block for the synthesis of valuable chemicals, including propylene glycol (PG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…According to James [ 32 ] amino acids adsorb in Pd centers. Our studies on sugar beet pulp hydrolysates showed the presence of Ala, Pro in the concentrations over 110 mmol/L; Leu, Tyr over 80 mmol/L and Asp, Glu, Gly, His, Arg, Val, Cys, Phe over 20 mmol/L [ 33 ]. Blocking the centers on the Pd surface could hinder the reduction of FA to THFA, which might explain the higher selectivity to FA observed for distillates obtained from beet leaves.…”
Section: Resultsmentioning
confidence: 99%
“…According to James [ 32 ] amino acids adsorb in Pd centers. Our studies on sugar beet pulp hydrolysates showed the presence of Ala, Pro in the concentrations over 110 mmol/L; Leu, Tyr over 80 mmol/L and Asp, Glu, Gly, His, Arg, Val, Cys, Phe over 20 mmol/L [ 33 ]. Blocking the centers on the Pd surface could hinder the reduction of FA to THFA, which might explain the higher selectivity to FA observed for distillates obtained from beet leaves.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is increasingly converted into bioproducts such as yeast biomass (6) or biogas (2). This study, conducted at Lodz University of Technology, shows for the first time that SBP is also a promising feedstock for lactic acid biosynthesis (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…However, some disadvantages may occur during scaling-up. The separate hydrolysis of sugar beet pulp was successfully implemented in a 3 m 3 stirred reactor at the Sugar factory in Dobrzelin (7,42,43), but with smaller enzyme doses such parameters as the presence of a dispersed gas phase and turbulent flow may be more significant for the efficiency of the process.…”
Section: Separate Hydrolysis and Fermentation (Shf)mentioning
confidence: 99%
“…The biomass was saccharified in a 3 m 3 reactor for 16 h at 50 • C, using a mixture (1:1) of two multi-enzyme preparations made by Novozymes: Viscozyme ® (Bagsvaerd, Denmark) and Ultraflo ® Max (Bagsvaerd, Denmark) (0.03 L/kg of sugar beet pulp dry weight). Saccharification was stopped by heating (80 • C for 10 min) [44].…”
Section: Feedstock: Sugar Beet Pulp Hydrolyzatementioning
confidence: 99%